Enhancing CO2-Valorization Using Clostridium autoethanogenum for Sustainable Fuel and Chemicals Production - Heffernan, James K.; Valgepea, Kaspar; de Souza Pinto Lemgruber, Renato; Casini, Isabella; Plan, Manuel; Tappel, Ryan; Simpson, Sean D.; Köpke, Michael; Nielsen, Lars K.; Marcellin, Esteban (Frontiers in Bioengineering and Biotechnology, 2020)
Acetogenic bacteria can convert waste gases into fuels and chemicals. Design of bioprocesses for waste carbon valorization requires quantification of steady-state carbon flows. Here, steady-state quantification of autotrophic chemostats containing Clostridium autoethanogenum grown on CO2 and H2 revealed that captured carbon (460 ± 80 mmol/gDCW/day) had a significant distribution to ethanol (54 ± 3 C-mol% with a 2.4 ± 0.3 g/L titer). We were impressed with this initial result, but also observed limitations to biomass concentration and growth rate. Metabolic modeling predicted culture performance and indicated significant metabolic adjustments when compared to fermentation with CO as the carbon source. Moreover, modeling highlighted flux to pyruvate, and subsequently reduced ferredoxin, as a target for improving CO2 and H2 fermentation. Supplementation with a small amount of CO enabled co-utilization with CO2, and enhanced CO2 fermentation performance significantly, while maintaining an industrially relevant product profile. Additionally, the highest specific flux through the Wood-Ljungdahl pathway was observed during co-utilization of CO2 and CO. Furthermore, the addition of CO led to superior CO2-valorizing characteristics (9.7 ± 0.4 g/L ethanol with a 66 ± 2 C-mol% distribution, and 540 ± 20 mmol CO2/gDCW/day). Similar industrial processes are commercial or currently being scaled up, indicating CO-supplemented CO2 and H2 fermentation has high potential for sustainable fuel and chemical production. This work also provides a reference dataset to advance our understanding of CO2 gas fermentation, which can contribute to mitigating climate change.